The Role of Madrasah Principles and School Culture in Enhancing Teacher Performance at Muhammadiyah Schools - Abd. Rahman; Mowafg Masuwd; Mohd Aizul Yaakob; Hasanuddin Hasanuddin (Universitas Muhammadiyah Mataram, 2026)
This study examines how madrasah principals' leadership practices and school culture shape teacher performance in Muhammadiyah schools in South Sulawesi, Indonesia. While previous studies have extensively addressed leadership and school culture, evidence remains limited regarding the specific mechanisms by which faith-based leadership in Muhammadiyah madrasahs is manifested and experienced at the school level, particularly outside of key areas. Addressing this gap is crucial because leadership and culture are practical levers for strengthening teacher development and maintaining school quality in a values-based educational environment. This study employed a qualitative multiple case study design in three Muhammadiyah madrasahs in South Sulawesi. Data were collected through in-depth interviews with participants (madrasah principals, vice-principals, and teachers) who were purposively selected based on criteria such as position, minimum tenure, integration into professional development programs, and non-participant observation and document analysis (e.g., school policies and professional development records). Data were analyzed using thematic analysis through iterative coding, theme development, and cross-case comparison. Findings indicate that principals support teacher performance through (1) structured professional development planning (e.g., training/workshops aligned with teacher needs), (2) instructional supervision and feedback routines, (3) cultivating a collaborative culture (peer support, shared problem-solving), and (4) recognition practices that strengthen motivation and commitment. Based on these themes, we recommend strengthening needs-based professional development cycles, institutionalizing regular feedback and supervision protocols, and implementing transparent recognition criteria aligned with agreed-upon performance indicators.